1990
DOI: 10.1155/1991/139202
|View full text |Cite
|
Sign up to set email alerts
|

Pyuria in Institutionalized Elderly Subjects

Abstract: in institutionalized e lderly subjects. Can J Infe ct Dis 199 1;2(4 ):142-146. Two hundred and forty-three wine specimens from 76 elderly institutionalized residents were obtained for urine culture, quantitative leukocyte count and winalysis. Significant bacteriuria was present in 153 specimens (63%), including 33 (22%) with more than one organism. Pyuria (greater than or equal to 10 leukocytes/mm3 ) was present in 214 specimens (88%). including 116 (97%) with single organism bacteriuria, 27 (82%) with multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
1

Year Published

1993
1993
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 13 publications
1
9
1
Order By: Relevance
“…In addition to its high prevalence, we found that pyuria is commonly present in the absence of bacteriuria. Although our prevalence rates of pyuria and bacteriuria differ somewhat from previous studies of institutionalized women 5 and men, 4 in which pyuria was defined quantitatively rather than by standard clinical laboratory techniques, our data do support the conclusions of these studies: pyuria is not predictive of bacteriuria in the nursing home population. This also appears to be true in spinal cord injured patients who are on intermittent catheterization 12 …”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…In addition to its high prevalence, we found that pyuria is commonly present in the absence of bacteriuria. Although our prevalence rates of pyuria and bacteriuria differ somewhat from previous studies of institutionalized women 5 and men, 4 in which pyuria was defined quantitatively rather than by standard clinical laboratory techniques, our data do support the conclusions of these studies: pyuria is not predictive of bacteriuria in the nursing home population. This also appears to be true in spinal cord injured patients who are on intermittent catheterization 12 …”
Section: Discussioncontrasting
confidence: 75%
“…Pyuria is often used by clinicians to determine if bacteriuria should be treated, yet few studies have examined the prevalence and meaning of pyuria in the nursing home population. One study in a predominantly male, asymptomatic nursing home population found that 93% of bacteriuric specimens and 59% of sterile specimens had pyuria 4 . Another study, which involved 52 female nursing home residents, found a prevalence of pyuria of 50%; of those with pyuria, 73% had sterile urine, and of those with sterile urine, 43% had pyuria 5 .…”
mentioning
confidence: 99%
“…Thus, the presence of pyuria does not differentiate asymptomatic from symptomatic infection. In residents with persistent asymptomatic bacteriuria, a high degree of pyuria may persist for many years [9]. Approximately 30% of elderly nursing home residents without bacteriuria have pyuria [2].…”
Section: Diagnosismentioning
confidence: 99%
“…Cytokines Although ASB is asymptomatic by definition, it is not merely a colonization of bacteria in the urinary tract. ASB can be regarded as an asymptomatic infection, since ASB is associated with leukocyturia, elevated urinary cytokines, and an elevated urinary antibody to uropathogens [20,21]. However, the levels of cytokines/chemokines in the urine of elderly people with regard to ASB and acute cystitis have not yet been fully investigated.…”
mentioning
confidence: 99%